Leadership pure and simple [ how transformative leaders create winning organizations - Wilkins, David , 1971- (McGraw-Hill, 2013)
Gives you the tools to turn today's toughest business challenges into transformative opportunities for profitability and growth. This book addresses the broadest and important changes occurring in society today to help you develop strategies built around a central core that are reflective of local strategic variables